2021
DOI: 10.1002/jmv.27363
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of COVID‐19 in younger patients (May–July 2021)—An argument for extending vaccination?

Abstract: This hesitation is somewhat surprising, given the UK's previous "pioneering" decisions to offer just one vaccine dose initially, with variable intervals between first and second vaccine doses-as well as the ongoing school influenza immunization program in the UK (https://assets.publishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Since there is uncertainty about the long-term protective effect of the COVID-19 vaccine, exposing the children will not be a wise decision. Three articles ( 28 , 42 , 68 ) in this present review have shown negative concern about the duration of protection following COVID vaccination among children, whereas two were uncertain about it ( 48 , 58 ).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Since there is uncertainty about the long-term protective effect of the COVID-19 vaccine, exposing the children will not be a wise decision. Three articles ( 28 , 42 , 68 ) in this present review have shown negative concern about the duration of protection following COVID vaccination among children, whereas two were uncertain about it ( 48 , 58 ).…”
Section: Discussionmentioning
confidence: 72%
“…Frequent viral infections with other types of coronaviruses in the past, fewer ACE receptors or high activity of the ACE enzyme, well-developed thymus gland that produce very good T-cell and memory cell immunity, lower prevalence of comorbidity, high level of primary immunity by childhood vaccination, or cross-protection with BCG vaccination may be some of the factors behind it ( 1 , 100 , 112 – 115 ). In the present review, 27 articles ( 5 , 16 , 26 30 , 35 37 , 39 , 41 , 43 , 45 , 47 , 52 , 53 , 55 59 , 62 , 65 , 70 , 72 , 75 ) were highlighting the mild form of COVID-19 infection among children which prevents it from universal childhood COVID vaccination, whereas only 3 articles ( 42 , 48 , 64 ) were against it. However, Pulmonary embolism, myocarditis and cardiomyopathy, venous thromboembolism, acute or unspecific renal failure, Coagulation or hemorrhagic disorders, cardiac dysrhythmia, encephalopathy, and febrile seizures are some of the notable systemic complications of COVID among children ( 116 118 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations